2005
DOI: 10.1084/jem.20041330
|View full text |Cite
|
Sign up to set email alerts
|

Ets-1, a functional cofactor of T-bet, is essential for Th1 inflammatory responses

Abstract: To mount an effective type 1 immune response, type 1 T helper (Th1) cells must produce inflammatory cytokines and simultaneously suppress the expression of antiinflammatory cytokines. How these two processes are coordinately regulated at the molecular level is still unclear. In this paper, we show that the proto-oncogene E26 transformation–specific-1 (Ets-1) is necessary for T-bet to promote interferon-γ production and that Ets-1 is essential for mounting effective Th1 inflammatory responses in vivo. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(164 citation statements)
references
References 54 publications
9
152
1
2
Order By: Relevance
“…The list of transcription factors that activate IL10 production is increasing; however, only a handful of transcription factors are known to repress its expression (23). Transcription factors ETS1 and T-bet repress IL10 expression in Th1 cells, BCL-6 inhibits IL10 production in Th2 cells, MHC class II transactivator (CIITA) negatively regulates IL10 expression in mouse dendritic cells, and BCL-3 represses IL10 production in macrophages (23,(45)(46)(47)(48). However, the quest for master regulators with a direct binding site on the IL10 promoter still remains.…”
Section: Discussionmentioning
confidence: 99%
“…The list of transcription factors that activate IL10 production is increasing; however, only a handful of transcription factors are known to repress its expression (23). Transcription factors ETS1 and T-bet repress IL10 expression in Th1 cells, BCL-6 inhibits IL10 production in Th2 cells, MHC class II transactivator (CIITA) negatively regulates IL10 expression in mouse dendritic cells, and BCL-3 represses IL10 production in macrophages (23,(45)(46)(47)(48). However, the quest for master regulators with a direct binding site on the IL10 promoter still remains.…”
Section: Discussionmentioning
confidence: 99%
“…Surviving mice and chimeras derived from Ets1-targeted cells exhibit pan-lymphoid defects. These defects include reduced numbers of thymocytes, lymphoid cells in the spleen, and NK and NKT cells; loss of detectable NK and NKT cell activity; decreased proliferation and elevated apoptosis in mature T cells (4,6,40,58); increased differentiation of B cells to plasma cells with elevated serum immunoglobulin M; B-cell receptor signaling defects (12); abnormalities in T-cell receptor (TCR) ␤-selection in thymopoiesis; and an ineffective Th1 response (11,19). Complicating the assessment of Ets1 function is the fact that Ets1-null mice have been studied not only on a mixed genetic background (C57BL/6 ϫ 129Sv) predisposed to autoimmunity (53) but also with a line of Ets1-null mice that expresses a very low level of a neomorphic protein (ϳ1 to 5%) lacking the pointed domain of Ets1 (7,59).…”
mentioning
confidence: 99%
“…Previous studies in Ets-1 knockout (Ets-1KO) mice have demonstrated the important functions of Ets-1 in development, proliferation, and survival of NK and T cells (18)(19)(20). Furthermore, Ets-1 acts as a cofactor of T-bet and is essential for Th1 effector function and differentiation by regulating IFN-g expression (21). Ets-1 is a negative regulator of Th17 differentiation, and Th17 cells deficient of Ets-1 express increased IL-17 and IL-17-related cytokines (22).…”
Section: Naive Cd4mentioning
confidence: 99%
“…Flag-Ets-1 plasmid was described previously (21). The cDNA encoding Flag-Ets-1 was cloned into pLV-CAG-EGFP vector (kindly provided by Dr. Masahito Ikawa, Osaka University, Osaka, Japan).…”
Section: Plasmids and Luciferase Reporter Assaysmentioning
confidence: 99%